2015
DOI: 10.1016/j.marchem.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic approach to assess the strengths of ligands bound to soluble Mn(III)

Abstract: The soluble porphyrin ligand [, , ,  -tetrakis(4-carboxyphenyl)porphine (T(4-CP)P)] was used as a competitive complexing ligand to study Mn speciation in the sediment porewaters of four stations in the Laurentian Trough. Both Mn(II) and Mn(III) concentrations were determined simultaneously. The rate of recovery of Mn(II) complexes by the porphyrin shows similar kinetics, but Mn(III)-ligand complexes give different values for the kinetics of recovery, which can be used along with the steady-state approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…Fourthly, it has been suggested that dissolved Mn ligands keep Mn in solution (Sander and Koschinsky, 2011;Madison et al, 2013;Luther et al, 2015). That would result in less conversion to manganese oxide aggregates, and hence may solve the removal problem, but this would yield wrong Mn ox /Mn diss concentration ratios like we saw for Ox-idThreshold.…”
Section: Export Dynamicsmentioning
confidence: 77%
See 1 more Smart Citation
“…Fourthly, it has been suggested that dissolved Mn ligands keep Mn in solution (Sander and Koschinsky, 2011;Madison et al, 2013;Luther et al, 2015). That would result in less conversion to manganese oxide aggregates, and hence may solve the removal problem, but this would yield wrong Mn ox /Mn diss concentration ratios like we saw for Ox-idThreshold.…”
Section: Export Dynamicsmentioning
confidence: 77%
“…The complete process may be more complicated than described above (Boyle et al, 2005), e.g. because Mn binds to dissolved ligands such that more of it may stay in solution (Sander and Koschinsky, 2011;Madison et al, 2013;Luther et al, 2015). Manganese oxides are important scavengers of other trace metals like iron, cobalt, nickel and zinc (Yamagata and Iwashima, 1963;Murray, 1975;Means et al, 1978;Saito et al, 2004;Tonkin et al, 2004), as well as insoluble radionuclides such as thorium and protactinium (e.g Reid et al, 1979;Hayes et al, 2015;Jeandel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…All samples were analyzed for soluble Mn speciation within two hours of collection following the addition of a soluble porphyrin ligand [α, β, γ, δ-tetrakis(4-carboxyphenyl)porphine (T(4-CP)P)] , according to the method described by Madison et al (2011). The method allows for the subsequent spectrophotometric determination of both Mn(II) and Mn(III)-L weak (Mn(III)-L weak can be outcompeted by the added porphyrin ligand, and has logK cond <13.2; Oldham et al, 2015;Luther et al, 2015) using the differential kinetics of the reaction between Mn and the added porphyrin which is initially complexed to Cd(II). The Mn(II) displaces the Cd(II) and reacts rapidly with the porphyrin, forming a Mn(III)-porphyrin complex as Mn(II) oxidizes in the presence of oxygen, whereas the Mn(III)-L weak undergoes a ligand substitution reaction with the porphyrin to form the Mn(III)-porphyrin complex (logK cond <13.2, Oldham et al, 2015;.…”
Section: Dissolved Mn Speciationmentioning
confidence: 99%
“…In fact, these Mn(III)‐L complexes have recently been shown to be a dominant component of dissolved Mn within estuaries and ocean basins (Trouwborst et al, ; Dellwig et al, ; Yakushev et al, ; Madison et al, , ; Oldham et al, , 2017a,b,c). Additionally, Mn(III) has been shown to bind to the same ligands as Fe(III) (Duckworth & Sposito, , ; Parker et al, ) with stability constants similar to or exceeding those of analogous Fe(III)‐L complexes (Luther et al, ). Thus, Mn(III)‐L complexes are now considered to be an important part of the Mn pool and may be a particularly reactive fraction as they can both donate and accept electrons.…”
Section: Introductionmentioning
confidence: 99%